Judicial Activism in a Violent Context: The Origin, Role, and Impact of the Colombian Constitutional Court - Manuel José Cepeda-Espinosa (Washington University Global Studies Law Review, 2004)
My intention in this overview is to describe generally the origins and impact of the Constitutional Court and its main decisions. I will also provide a general overview of its role within the Colombian system-a comprehensive assessment that has not been fully carried out to date and that obviously requires much more space and time than is available for this specific presentation.
Keywords: Constitutional law; Judicial activism; Judicial review; Colombia